Molecular surveillance of Bordetella pertussis during the 2024 outbreak in Southeast Brazil: allelic profiles and comparison to vaccine strain - Thiago J. Sousa; Felipe D. Gatti; Joana Z. Nodari; Gabriela C. de Mendonça; Anna Clara G. Có; Thabata C. D. Damasceno; Nayara C. Silva; Lílian S. Lavagnoli; Danielle G. P. Lyra; Jaqueline P. Goulart; Rodrigo Ribeiro-Rodrigues (Brazilian Journal of Microbiology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Microscale sealed vessel (MSSV) technique in petroleum systems: a review - Sandra B. Jorge; André L.S. Pestilho; Juliana M. Sousa; Antônia M. Corrêa; Hemmely G. de S. Severino; Alice Maria S. Rodrigues; Kátia Z. Leal; Cleverson J.F. de Oliveira; Daniel S. Dubois; Marcelo C. Bernardes (Organic Geochemistry, 2026)

WITHDRAWN: Inflammatory markers levels and clinical characteristics in COVID-19 susceptibility and severity: A cross-sectional multicentric study - Lucas C. Pedro; Camila O. Arent; Flávia S. Niero; Caion A. Rodrigues; Margarete D. Bagatini; Gabriela G. de Oliveira; Zuleide Maria Ignácio; Larissa Joaquim; Fabricia Petronilho; João Quevedo; Alexandra I. Zugno; Luciane B. Ceretta; et al. (Next Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Luteal features and serum concentrations of progesterone and hCG in dairy goats submitted to estrus induction followed by intrauterine or intramuscular hCG administration - Alice L. Martins; Luana R. Côrtes; Juliana N.D. Rodrigues; Paulo Sergio C. Rangel; Ana Lucia R. e S. Maia; Felipe Z. Brandão; Luiz Gustavo B. Siqueira; Bruna W. de Freitas; Jeferson F. Fonseca (Domestic Animal Endocrinology, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Pre-exposure of Lactobacillus acidophilus to stress conditions impacts the metabolites and bioaccessibility of calcium and carotenoids in fermented dairy products - Juliana S. Graça; Joyce G.S. Silva; Laísa G. Dias; Ana Augusta Odorissi Xavier; Elenilson G. Alves-Filho; Tatiana C. Pimentel; Edy S. Brito; Sueli Rodrigues; Juliana A.L. Pallone; Lilian R.B. Mariutti; Adriana Z. Mercadante; Neura Bragagnolo; et al. (Food Research International, 2025)

Current constraints to reconcile tropical forest restoration and bioeconomy - Pedro Medrado Krainovic; Diego Oliveira Brandão; Angélica Faria Resende; Stella Z. Schons; Leonardo Munhoz; Jean Paul Metzger; Nathália C. Nascimento; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion; Joannès Guillemot; Sergio de-Miguel (Sustainability Science, 2025)
Large-scale forest restoration is vital for delivering a broad array of ecosystem services benefits to society. However, it is often perceived as an economically noncompetitive land use choice. Integrating economic opportunities into restoration aligns socioeconomic and environmental goals, reducing conflicts between forest production and conservation-oriented management decisions. Supply chains focusing on high-value goods can enhance the reach of forest restoration efforts and unite ecological and economic benefits in a multifunctional manner. The bioeconomy has emerged as a potential but critical driver for attracting investments in restoration. We outline the challenges and solutions to reconcile forest restoration and bioeconomy, specifically about (i) native timber production, (ii) non-timber forest products, (iii) biotechnological products, and (iv) intangible ecosystem services. This requires collaborative and multidisciplinary efforts to improve investment in large-scale projects. The intricacies of these issues intersect with research development, market dynamics, legal frameworks, and regulatory paradigms, underscoring the necessity for nuanced and tailored public policy interventions. These integrated approaches should enable tropical countries to lead the global forest-based economy and usher in a new era of forest restoration. Graphical abstract

Airborne DNA: State of the art – Established methods and missing pieces in the molecular genetic detection of airborne microorganisms, viruses and plant particles - C.-E. Pogner; C. Antunes; G.P. Apangu; N. Bruffaerts; S. Celenk; A. Cristofori; N. González Roldán; A. Grinn-Gofroń; B. Lara; M. Lika; D. Magyar; M. Martinez-Bracero; et al. (Science of The Total Environment, 2024)

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Where is ocean literacy in oceanic islands’ schools? The Azores case - Ana C. Costa; Diana Freitas; Ana I. Santos; Andrea Z. Botelho; Manuela I. Parente; André Behr; Ana M. Rodrigues; Hélia Guerra; José Cascalho; Armando Mendes (Marine Policy, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Extraction of phenolic compounds from grape pomace using ohmic heating: Chemical composition, bioactivity and bioaccessibility - P. Ferreira-Santos; C. Nobre; R.M. Rodrigues; Z. Genisheva; C. Botelho; J.A. Teixeira (Food Chemistry, 2024)

Cerrado deforestation threatens regional climate and water availability for agriculture and ecosystems - Ariane A. Rodrigues; Marcia N. Macedo; Divino V. Silvério; Leandro Maracahipes; Michael T. Coe; Paulo M. Brando; Julia Z. Shimbo; Raoni Rajão; Britaldo Soares‐Filho; Mercedes M. C. Bustamante (Global Change Biology, 2022)
The Brazilian Cerrado is one of the most biodiverse savannas in the world, yet 46% of its original cover has been cleared to make way for crops and pastures. These extensive land‐use transitions (LUTs) are expected to influence regional climate by reducing evapotranspiration (ET), increasing land surface temperature (LST), and ultimately reducing precipitation. Here, we quantify the impacts of LUTs on ET and LST in the Cerrado by combining MODIS satellite data with annual land use and land cover maps from 2006 to 2019. We performed regression analyses to quantify the effects of six common LUTs on ET and LST across the entire gradient of Cerrado landscapes. Results indicate that clearing forests for cropland or pasture increased average LST by ~3.5°C and reduced mean annual ET by 44% and 39%, respectively. Transitions from woody savannas to cropland or pasture increased average LST by 1.9°C and reduced mean annual ET by 27% and 21%, respectively. Converting native grasslands to cropland or pasture increased average LST by 0.9 and 0.6°C, respectively. Conversely, grassland‐to‐pasture transitions increased mean annual ET by 15%. To date, land changes have caused a 10% reduction in water recycled to the atmosphere annually and a 0.9°C increase in average LST across the biome, compared to the historic baseline under native vegetation. Global climate changes from increased atmospheric greenhouse gas concentrations will only exacerbate these effects. Considering potential future scenarios, we found that abandoning deforestation control policies or allowing legal deforestation to continue (at least 28.4 Mha) would further reduce yearly ET (by −9% and −3%, respectively) and increase average LST (by +0.7 and +0.3°C, respectively) by 2050. In contrast, policies encouraging zero deforestation and restoration of the 5.2 Mha of illegally deforested areas would partially offset the warming and drying impacts of land‐use change.

Sugarcane: A Promising Source of Green Carbon in the Circular Bioeconomy - Susan G. Karp; Walter J. M. Burgos; Luciana P. S. Vandenberghe; Kim V. Diestra; Luis A. Z. Torres; Adenise L. Woiciechowski; Luiz A. J. Letti; Gilberto V. M. Pereira; Vanete Thomaz-Soccol; Cristine Rodrigues; Júlio C. de Carvalho; Carlos R. Soccol (Sugar Tech, 2022)

Asynchrony, density dependence, and persistence in an amphibian - Freya E. Rowland; Elizabeth S. Schyling; L. Kealoha Freidenburg; Mark C. Urban; Jonathan L. Richardson; A. Z. Andis Arietta; Susan B. Rodrigues; Adriana D. Rubinstein; Michael F. Benard; David K. Skelly (Ecology, 2022)
Understanding drivers of metapopulation dynamics remains a critical challenge for ecology and conservation. In particular, the degree of synchrony in metapopulation dynamics determines how resilient a metapopulation is to a widespread disturbance. In this study, we used 21 years of egg mass count data across 64 nonpermanent freshwater ponds in Connecticut, USA to evaluate patterns of abundance and growth and to assess regional as well as local factors in shaping the population dynamics of wood frogs ( Rana sylvatica = Lithobates sylvaticus ). In particular, we asked whether a species known to undergo metapopulation dynamics exhibited spatial synchrony in abundances. With the exception of a single year when breeding took place during severe drought conditions, our analyses revealed no evidence of synchrony despite close proximity (mean minimum distance

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Important Key Process Simulations in the Field of Steel Metallurgy - A. Ludwig; C. M. G. Rodrigues; Z. Zhang; H. Zhang; E. Karimi-Sibaki; H. Barati; A. Vakhrushev; M. Al-Nasser; M. Wu; A. Kharicha (BHM Berg- und Hüttenmännische Monatshefte, 2022)
During the last decade, the chair for ‘Simulation and Modelling of Metallurgical Processes’ (SMMP) has worked on different metallurgical processes with the highlights of the following five industrial relevant topics: (i) modelling the as-cast structures of large steel castings; (ii) exploring the formation mechanisms of macrosegregation; (iii) describing magnetohydrodynamic and electrochemical phenomena in remelting processes, (iv) understanding how solidification and flow can be influenced by magnetohydrodynamics during steel continuous casting; and (v) describing nozzle clogging in steelmaking processes. In this contribution, the main achievements from the group on the above five topics are briefly described.

Natural Enemies of the Harrisia Cactus Mealybug and Other Hypogeococcus Species (Hemiptera: Pseudococcidae) in Puerto Rico: Identification and Taxonomic Notes on Primary and Secondary Parasitoids - S. V. Triapitsyn; S. D. Hight; G. A. Logarzo; M. B. Aguirre; J. C. Verle Rodrigues; V. A. Trjapitzin; Z. Rivera Ocasio; M. L. Rivera-Vázquez; M. J. West Ortiz; Y. Rodríguez Reyes (Neotropical Entomology, 2020)

Deleterious effects of chronic mercury exposure on in vitro LTP, memory process, and oxidative stress - Leandro F. Oliveira; Laís D. Rodrigues; Giancarlo M. Cardillo; Mariana B. Nejm; Marcia Guimarães-Marques; Selvin Z. Reyes-Garcia; Karolini Zuqui; Dalton V. Vassallo; Ana C. Fiorini; Carla A. Scorza; Fulvio A. Scorza (Environmental Science and Pollution Research, 2020)

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.